CLASSIC PROBLEMS: PENGENDALIAN PERSEDIAAN - Kun Ismawati (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2019)
This research aims determine the effectiveness of merchandise inventory control system at CV. Berkat Abadi Solo by using the method of economic order quantity, reoder point and safety stock. Data collection techniques used are interviews and documentation. Data analytical technique by using descriptive quantitative. The methods used in this research were economic order quantity, reoder point dan safety stock. The results of this study can be concluded that the control effectiveness inventory of merchandise at CV. Berkat Abadi Solo reviewed from the economic order quantity, reoder point dan safety stock method was still not achieved.